COMPARATIVE STUDY OF STRAIGHT LINE METHOD, DOUBLE DECLINING BALANCE METHOD, AND SUM OF THE YEARS DIGIT METHOD IN FIXED ASSETS OF PT. MORO DJOYO GAS - Yely Sulistyawati; Hery Suprayitno (Universitas Islam Balitar, 2020)
Moro Djoyo Gas is a company engaged in the trade of 3kg LPG gas. In carrying out its company’s operational activities cannot be separated from the use of various equipment and vehicles included in fixed assets. Therefore, there needs to be a permanent management of fixed assets so it can be utilized according to company needs. The purpose of this study is to determine the depreciation of fixed assets used by PT. Moro Djoyo gas, to find out the profits obtained by using other depreciation methods, as well as comparing, recommending, and giving reasons for the appropriate depreciation method for PT. Moro Djoyo Gas. The research method used is qualitative with comparative analysis techniques. The results of the study stated that the percentage method used by the company was less effective. PT. Moro Djoyo Gas should use the double declining balance method, which its profit will remain relatively constant each year.